(untitled) - Maeder, Roman E. (Reading, Mass, 1991)
Programming in mathematica is unlike any you have encountered before.The manual explains all its features and gives some very basic examples of their use.
Keywords: Khoa học,Science, Mathematica (Computer program language); Xử lý dữ liệu,Data processing